The Ability of Professional Standards to Mitigate Aggressive Reporting - Cuccia, Andrew D.; Hackenbrack, Karl; Nelson, Mark W. (The Accounting Review, 1995)
[This paper investigates whether replacing a standard that employs a vague, verbal disclosure threshold with a standard that employs a more stringent, numerical threshold mitigates the aggressiveness of reporting decisions. Two experiments were performed in a tax setting. The results indicate that (1) when a verbal standard is in place, tax practitioners use the latitude inherent in a verbal standard to support aggressive reporting decisions, and (2) when a numerical standard is in place, tax practitioners use instead the latitude available in assessing evidential support to justify an aggressive reporting decision. This shift in incentive effect is pronounced enough to render reporting decisions made under the numerical standard as aggressive as reporting decisions made under the verbal standard. These results indicate that replacing verbal thresholds with numerical thresholds may not diminish the aggressiveness of reporting decisions.]